The effect of sports games on the development of the physical qualities of preschool children - Ihor Bohdanovskiy (Kazimierz Wielki University, 2021)
The study is devoted to the search for effective and affordable means for the development of physical qualities of children of senior preschool age. The influence of various sports games on the development of speed, agility, endurance, flexibility and muscle strength is shown. It has been proven that sports games should be selected taking into account the anatomical and physiological characteristics of children of senior school age. The article presents the characteristics and structural elements of various sports games, taking into account the age of children. It has been confirmed that the activity of children in the minds of raptly changing conditions is to occupy the mind with sports games until the manifestation of a complex of psycho-physiological functions: sensorimotor reaction, reception and processing of information, kinesthetic, operative thought, respect, the process of establishing and perfecting dynamic stereotypes. A generalizing conclusion is made about the optimal use of sports games for the development of physical qualities in children of senior preschool age.